KONSEP PRODUK MURABAHAH DALAM PERSPEKTIF EKONOMI SYARI’AH - Ika Trisnawati Alawiyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2016)
Business development to financial services syariah have made progress and development that was so advanced. Of a lot of syariah commercial banks standing, there were also a lot cooperatives syariah or the Baitul Maal Wattamwil (BMT) stand around the community in fact closer with the community. Bank syariah is a financial syariah that serves facilitate economy mechanism in the real sector through activity business activities (an investment , buying and selling or forth based on syariah principle , namely rules agreement islamic law based on the principle for the, fee ,ujroh and the margin. This research is research library (library research), by using the method descriptive qualitative. Conclusion this research is well murabahah products in perspective economic syariah namely products mutually beneficial between customers with the bank syariah or local BMT who use the murabahah. Fiqih an order of Hanafi, marghiani (w. 593 / 1197), confirming the validity of murabahah based on the terms of what is important to the validity of a trading is in murabahah, and also because people need it, faqih of madhzab Syafi’i, Nawawi (w. 676 / 1277) just say “ murabahah is may without no opposition in the least “. With the that product a large number of residents helped in advance business is by applying of the financing in a financial institutions such as bank about the manner of syari’ah and others.